Penanaman Nilai-Nilai Karakter Pada Remaja (Studi Analisis Kitab ‘Iẓah anNāsyi’īn Karya Syaikh Muṣṭafa al-Gulāyainī) - Rafita Utari; Kadar Kadar; Andi Murniati (Instructional Development Journal, 2021)
The Character education is currently a major issue in the world of education. Apart from being part of the process of shaping the character of the nation, character education is also expected to be the main foundation in increasing the degree and dignity of the indonesian nation. The character education that is embedded in the soul is expected to be able to form a personality with noble character in accordance with the guidance of Al-Quran and As-Sunnah. Syaikh Muṣṭafa al-Gulāyainī dalam  kitab ‘Iẓah an-Nāsyi’īnstates that there are two character values in youth, namely good character that must be cultivatedand bad characters that must be avoided. The good characters that must be cultivated include, namely: patient, sincerity, hope, courage, religion, nationalism, simplicity, carrying out obligations, helping out, Keep doing and tawakal, self-confidence. The bad characters to avoid include: hypocrisy, despair, cunning, carelessness, delude by one’s own feeling, wasted dan hasad. The educational process requires educational methods that are able to cultivate good character values, some arestory method, the hiwar or conversation method, the parable method, the exemplary method, the habituation method, the lecture method, the advice method, the command and  prohibition method . Third, the factors that influence the character of youth in the kitab‘Iẓah an-Nāsyi’īnkarya Syaikh Muṣṭafa al-Gulāyainī. There are four factors that influence the character of youth, namely : yourself, parents, school and society